(untitled) (PETITUM, 2022)
ABSTRACT: This study aims to determine how the implementation of district regulations. Tangerang No. 4 of 2012 between the developer of Talaga Bestari and the local government of Tangerang Regency. In Tangerang Regency, public facilities and housing facilities must be handed over by the developer to the local government. However, there are still housing developers who have not submitted public facilities and social facilities for housing, this is a problem because the Tangerang district government’s policy has not been successful in controlling housing social facilities. This study uses qualitative methods with observation techniques and direct interviews with informants related to research problems. Sources of data obtained from primary data that is sourced from interviews or observations and also secondary data from journals or electronic media. The data obtained will be analyzed by collecting or selecting data that is in accordance with the reality in the field. The existence of obstacles in the general requirements, namely the fulfillment of the site plan site is a factor that Talaga Bestari’s developer has not been able to hand over the housing and social housing cluster housing to the local government of Tangerang Regency. ABSTRAK: Penelitian ini bertujuan untuk mengetahui bagaimana implementasi perda Kab. Tangerang No. 4 Tahun 2012 antara pengembang Talaga Bestari dan pemda Kabupaten Tangerang. Di Kabupaten Tangerang fasum dan fasos perumahan wajib diserahkan pengembang kepada pemerintah daerah. Tetapi masih ada pengembang perumahan yang belum menyerahkan fasum dam fasos perumahan, hal tersebut menjadi masalah dikarenakan belum berhasilnya kebijakan pemda kabupaten Tangerang tentang penertiban fasum fasos perumahan. Penelitian ini menggunakan metode kualitatif dengan teknik observasi dan wawancara langsung kepada informan terkait masalah penelitian. Sumber data yang didapatkan dari data primer yaitu bersumber dari wawancara atau observasi dan juga data sekunder dari jurnal atau media elektronik. Data yang didapatkan akan dianalisis dengan cara mengumpulkan atau menyeleksi data yang sesuai dengan kenyataan dilapangan. adanya kendala dalam peryaratan umum yaitu pemenuhan tapak siteplan menjadi faktor pengembang Talaga Bestari belum bisa menyerahkan fasum dan fasos cluster perumahan kepada pemerintah daerah Kabupaten Tangerang.